2016
DOI: 10.1038/sc.2016.33
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in Swiss elite wheelchair athletes

Abstract: A high percentage of vitamin D deficiency was found among Swiss elite wheelchair athletes. Conclusively, we recommend supplementation with vitamin D-especially during winter-to prevent a deficiency and an impairment of performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 30 publications
(41 reference statements)
1
23
0
2
Order By: Relevance
“…Similar to the studies with able-bodied individuals, a high prevalence of vitamin D deficiency or insufficiency was found in patients [24] and athletes [25,26] with a spinal cord injury. Due to the impairment of the spinal cord, muscle strength might already be decreased and an additional impairment through vitamin D deficiency needs to be avoided.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…Similar to the studies with able-bodied individuals, a high prevalence of vitamin D deficiency or insufficiency was found in patients [24] and athletes [25,26] with a spinal cord injury. Due to the impairment of the spinal cord, muscle strength might already be decreased and an additional impairment through vitamin D deficiency needs to be avoided.…”
Section: Introductionsupporting
confidence: 75%
“…The prevalence of vitamin D deficiency was even higher in indoor wheelchair athletes compared to outdoor athletes [25]. Nevertheless, it was surprising that all recruited athletes in the present study showed a deficient vitamin D status at baseline (44 ± 18 nmol/L).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In addition, parathyroid hormone concentration decreased significantly in these individuals. Two studies showed a higher prevalence of vitamin D deficiency during the winter months, 21,34 whereas two other studies resulted in a lower vitamin D status in African Americans compared with that in Caucasians. 34,35 A significantly lower vitamin D status was detected in patients compared with that in controls, 26,28,33 whereas Vaziri, Pandian 25 did not find any difference between individuals with a SCI and able-bodied controls regarding vitamin D status.…”
Section: Resultsmentioning
confidence: 97%
“…Two studies investigated the vitamin D status in elite wheelchair athletes. 21,22 Two studies investigated vitamin D status in individuals with an acute SCI (o9 months). Most studies used 50 nmol l − 1 (20 ng ml − 1 ) as the threshold for vitamin D deficiency and 75 nmol l − 1 (30 ng ml − 1 ) for suboptimal or insufficient vitamin D status.…”
Section: Resultsmentioning
confidence: 99%